Arctic ship-based evidence of new particle formation events in the Chukchi and East Siberian Seas. (15th February 2020) - Dall'Osto, M.; Park, Jiyeon; Kim, Joo-Hong; Kang, Sung-Ho; Park, Kihong; Beddows, D.C.S.; Harrison, Roy M.; Yoon, Y.J.
Abstract: Arctic aerosol-climate interactions are controlled by multiple factors including sources, processes and removal mechanisms of particles. The Arctic is mostly ocean, surrounded by mostly land, and our understanding of Arctic aerosol processes is incomplete due to scarce measurements carried out in sea ice regions. In particular, it is currently not known if these particular regions are sources of aerosols of primary or secondary origin. We present new results from ship-based measurements illustrating that marine new particle production and growth events occur in open ocean and melting sea ice regions in the Chukchi and East Siberian Seas. We report two new particle formation events during which a recently formed nucleation mode (<15 nm diameter) is detected and is observed to slowly grow into an Aitken mode (0.1–3.8 nm h −1) . Our results suggest that new particle formation occurs in the marine boundary layer contributing to the Arctic aerosol population in the study region for the first time studied and herein reported. Highlights: Particle size distributions were collected during an Arctic ocean cruise. Elevated concentrations of aerosols (N < 100 up to 3, 000 cm −3 ) were found. New particle formation events associated with open ocean and sea ice regions.